A longitudinal comparison of symptom-distress and person-centeredness between a fast-track programme for cardiac surgery and conventional care - Marita Dalvindt; Shahab Nozohoor; Anna Forsberg; Martina Lundmark (PLoS ONE, 2026)
Aim and design Impaired recovery in the post-operative phase after cardiac surgery predicts long-term recovery, making it important to identify and treat symptoms immediately. A fast-track programme after cardiac surgery was implemented. When developing such programmes, the patients’ perspective of perioperative care is of major importance. This is a non-randomized longitudinal observational study in which symptom distress, perceived person-centeredness and pain level were prospectively compared after cardiac surgery. The aim of this non-randomized longitudinal observational study is to prospectively compare symptom-distress, perceived person-centeredness and pain level after cardiac surgery between a fast-track group and those undergoing conventional postoperative care. Methods Symptom distress was explored and compared between a fast-track group and those undergoing conventional postoperative care. A total of 149 participants, 75% men and 25% women, with a mean age of 67 years (SD 9.9 years), were included. The control group comprised 117 patients and the fast-track group 31. Symptom distress was assessed by the Post-Operative Recovery Profile Instrument, person-centeredness by the Being Taken Seriously Questionnaire, while a Numerical Rating Scale was employed to measure self-rated pain. Results Regarding symptom distress, the control group felt significantly (p = .041) more restricted in physical activity in the thoracic intensive care unit (TICU) compared to the fast-track group. However, no differences in symptom distress between the groups were reported in the surgical ward. Longitudinally, an increase in symptom distress was found in the TICU, followed by improvements at the surgical ward. The fast-track group demonstrated lower pain ratings at all time points compared to the control group. The pain intensity score was relatively high during the first six hours after extubation. There was no difference between the control group and the fast-track group regarding their experiences of receiving person-centred care at either of the two time points. Conclusions A fast-track programme is equivalent to conventional care in terms of perceived symptom-distress and person-centeredness and also reduces the duration of ICU care. Impact and patient contribution Detailed information regarding symptom distress could be used as an evidence-based foundation for symptom management support. The results contribute to an understanding of expected symptom patterns during cardiac surgery, which might increase self-efficacy when used to inform and educate patients perioperatively.